Critical Legal Studies: Memahami Hubungan Antara Kepentingan Bisnis, Pemerintah dan Hukum: Critical Legal Studies: Memahami Hubungan Antara Kepentingan Bisnis, Pemerintah dan Hukum - Trianto, Agus; Rosida, Nina; Wijaya, Endra (Mendapo: Journal of Administrative Law, 2023)
This study discusses several thoughts of Critical Legal Studies as a branch of thought in the field of law. This study uses conceptual and theoretical approach, and several opinions from law scholars are discussed. The Critical Legal Studies thinkers criticize the existing legal order, which they regard as a liberal order. In a liberal setting, Critical Legal Studies views law along with government entities in a broad sense, which form and implement law, as being subordinated to the interests of business actors. Thus, it will be difficult for the law and the government to truly be neutral and objective.